A method for preparing silicon-carbon composite material by mechanical stirring-free fluidized bed CVD

CN123002811APending Publication Date: 2026-10-30NINGBO NOTTINGHAM CHINA BEACONS OF EXCELLENCE RES & INNOVATION INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610844463.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

(1)破坏碳基体结构:机械搅拌叶轮在运转过程中会对脆性的碳基体颗粒(尤其是多孔碳)产生剧烈的撞击、挤压和剪切作用,容易导致其多孔骨架破碎、孔道坍塌,使其失去缓冲硅体积膨胀的核心功能,最终影响电池的循环寿命

Benefits of technology

1.实现了本质安全:彻底摒弃了机械搅拌装置,消除了反应器上最危险的动密封泄漏点,使得在处理高危气体时的安全等级得到根本性提升,为工艺的工业放大和长期稳定运行奠定了基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002811A_ABST
    Figure CN123002811A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing silicon-carbon composite material by mechanical-stirring-free fluidized bed CVD, and relates to the technical field of silicon-carbon composite material preparation, and comprises the following steps: S1, pretreatment and mixing: mixing carbon matrix material with fluidization aid particles accounting for 0.001%-99% of the mass of the carbon matrix material, so that the fluidization aid is attached to the surface of the carbon matrix to obtain modified carbon material; S2, silicon deposition: placing the modified carbon material in a fluidized bed reactor with mechanical-stirring-free inner components, heating to 300-1500 DEG C under inert atmosphere, and introducing silicon source gas to perform chemical vapor deposition until a predetermined silicon loading amount is reached; the fluidization aid particles replace mechanical stirring, and problems such as carbon matrix structure damage, gas leakage safety risk and equipment amplification difficulty caused by stirring in traditional fluidized bed CVD technology are fundamentally solved, and the prepared silicon-carbon composite material has the advantages of uniform silicon distribution, complete structure, good cycle stability and the like, and is suitable for high-performance lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of silicon-carbon composite material preparation technology, specifically a method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring. Background Technology

[0002] Silicon-carbon composite materials are considered core anode materials for next-generation high-energy-density lithium-ion batteries due to their theoretical specific capacity being far higher than that of traditional graphite. Among numerous preparation methods, chemical vapor deposition (CVD) can achieve uniform deposition and coating of silicon on carbon matrices (graphite, amorphous carbon, carbon nanotubes, graphene, porous carbon, etc.) at the nanometer or micrometer scale, thereby effectively mitigating the huge volume expansion of silicon during charging and discharging. This is a key technology for preparing high-performance silicon-carbon composite materials.

[0003] Choosing a suitable carbon matrix material facilitates efficient chemical vapor deposition (CVD) processes, resulting in uniformly deposited silicon-carbon composite materials. For example, porous carbon materials, due to their small particle size (ultrafine powder), are advantageous. D 50 <25μm, belonging to Geldart C-type particles), with a large specific surface area, exhibit unique properties and broad application prospects in the field of silicon-carbon composite materials. However, due to extremely strong interparticle forces (such as van der Waals forces), these particles have poor flowability, are prone to channeling and agglomeration, and are difficult to fluidize properly. This results in insufficient contact between the reactant gas and solid particles, uneven silicon deposition, and low reaction efficiency, severely restricting their application in lithium-ion battery materials.

[0004] To address this fluidization challenge, existing technologies generally incorporate mechanical stirring devices within the fluidized bed reactor to aid fluidization by mechanically breaking up particle agglomerations. However, this method suffers from the following inherent drawbacks that cannot be overcome: (1) Damage to carbon matrix structure: During operation, the mechanical stirring impeller will cause severe impact, compression and shearing on brittle carbon matrix particles (especially porous carbon), which can easily lead to the breakage of its porous skeleton and the collapse of its channels, causing it to lose its core function of buffering silicon volume expansion, and ultimately affecting the cycle life of the battery.

[0005] (2) Serious safety hazards exist: There must be a dynamic sealing point between the stirring shaft and the reactor shell. When handling flammable, explosive, highly toxic and dangerous gases such as silane and acetylene, this dynamic sealing point is a high-frequency leakage point, which can easily cause serious safety accidents such as combustion and explosion, posing a huge threat to personnel, equipment and environment.

[0006] (3) Restriction on industrial scale-up: The presence of mechanical stirring makes the reactor structure complex, the manufacturing cost high, and the energy consumption increased. Moreover, it is difficult to ensure uniform stirring of the entire bed in large-scale industrial plants, resulting in a significant process scale-up effect and making it impossible to achieve stable, economical, and large-scale continuous production.

[0007] Therefore, there is an urgent need in this field to develop a new fluidized bed CVD technology for preparing silicon-carbon composite materials that requires no mechanical stirring, can achieve efficient and stable fluidization of ultrafine carbon powder, and is inherently safe. Summary of the Invention

[0008] The purpose of this invention is to provide a method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring, so as to solve the problems mentioned in the background art.

[0009] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring, comprising the following steps: S1. Pretreatment and mixing: The carbon matrix material is mixed with fluidizing agent particles accounting for 0.001% to 99% of its mass, so that the fluidizing agent adheres to the surface of the carbon matrix, increases the interparticle spacing to reduce the interparticle forces, and obtains the modified carbon material. S2, Silicon deposition: The modified carbon material is placed in a fluidized bed reactor without mechanical stirring components, heated to 300-1500°C under an inert atmosphere, and silicon source gas is introduced for chemical vapor deposition until the predetermined silicon loading is reached. S3. Carbon coating: Carbon source gas is introduced into the fluidized bed reactor to perform carbon coating treatment on the silicon-carbon material deposited with silicon, thereby obtaining the silicon-carbon composite material.

[0010] As a preferred embodiment of the method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to the present invention, the carbon matrix material is one or more of porous carbon, graphite, amorphous carbon, carbon nanotubes, graphene, and carbon fiber.

[0011] As a preferred embodiment of the method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to the present invention, wherein: the fluidization aid particles are nanoparticles, coarse particles that are coarser than the carbon matrix, and mixed particles of nanoparticles and coarse particles, and the mass mixing ratio of the mixed particles of nanoparticles and coarse particles is not limited.

[0012] As a preferred embodiment of the method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to the present invention, the nanoparticle fluidization aid is one or more of silicon and silicon-containing compounds, high-performance carbon materials, conductive metal powders, metal oxide powders, and modified materials based thereon, pyrolysis reaction catalysts and modified materials based thereon, and the mass mixing ratio of various nanoparticles is not limited.

[0013] As a preferred embodiment of the method for preparing silicon-carbon composite materials by mechanically stirred fluidized bed CVD of the present invention, the coarse particle fluidization aid is one or more of silicon and silicon-containing compounds, high-performance carbon materials, conductive metal powders, metal oxide powders, and modified materials based thereon, silicon-carbon composite materials and modified materials based thereon, pyrolysis reaction catalysts and modified materials based thereon, and the mass mixing ratio of various coarse particles is not limited.

[0014] In a preferred embodiment of the method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to the present invention, the silicon source gas is one or more of silane, ethoxysilane, chlorosilane and other silicon-containing compounds.

[0015] In a preferred embodiment of the method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to the present invention, the carbon source gas is one or more of methane, ethane, ethylene, acetylene, propylene, and other carbon-containing organic compounds.

[0016] As a preferred embodiment of the method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to the present invention, in step S2, the chemical vapor deposition is a continuous process, which is carried out through multiple deposition-cooling cycles until the predetermined silicon loading is reached.

[0017] As a preferred embodiment of the method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to the present invention, wherein the silicon-carbon composite material is used as an active material to prepare a negative electrode sheet for a lithium-ion battery.

[0018] In a preferred embodiment of the method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to the present invention, the lithium-ion battery negative electrode sheet can be used as a component of a lithium-ion battery.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are: 1. Achieved inherent safety: The mechanical stirring device was completely eliminated, and the most dangerous dynamic seal leakage point on the reactor was eliminated, which fundamentally improved the safety level when handling high-risk gases, laying the foundation for the industrial scale-up and long-term stable operation of the process.

[0020] 2. Ensures the integrity of the material structure: The gentle fluidization aid particles-assisted fluidization method avoids physical damage to the microstructure of the carbon matrix by mechanical force, perfectly preserving the pore structure and buffering capacity of the carbon matrix (especially porous carbon), thus producing composite materials with better structure.

[0021] 3. Excellent fluidization effect and easy scale-up: Fluidization aid particles can significantly improve the fluidization quality of the bed with extremely low addition amounts, forming a uniform and stable fluidization state, high gas-solid contact efficiency, and uniform silicon deposition. This method does not rely on complex internal components, has simple equipment, and has a small scale-up effect, making it very suitable for large-scale continuous production.

[0022] 4. Synergistic improvement of electrochemical performance: The selected fluidization aids (such as metal powders, CNTs, etc.) have good conductivity and mechanical strength. Their presence in composite materials can build a better conductive network and further enhance the structural stability of the materials, thereby synergistically improving the rate performance and long cycle life of the battery. Attached Figure Description

[0023] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is a process flow diagram of a method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring, as per this invention patent. Figure 2 This is a SEM image of nanoparticles used as fluidization aids mixed with a carbon matrix in a method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring, as described in this invention patent. Figure 3 This is a comparison of the fluidization effect in a two-dimensional bed in a method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring, according to this invention patent (left: carbon matrix material without fluidization aid; right: the same carbon matrix material with fluidization aid). Detailed Implementation

[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Please see Figure 1 - Figure 3 This invention provides a technical solution: a method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring, comprising the following steps: S1. Pretreatment and mixing: The carbon matrix material is mixed with fluidizing agent particles accounting for 0.001% to 99% of its mass, so that the fluidizing agent adheres to the surface of the carbon matrix to obtain the modified carbon material. S2, Silicon deposition: The modified carbon material is placed in a fluidized bed reactor without mechanical stirring components, heated to 300-1500°C under an inert atmosphere, and silicon source gas is introduced for chemical vapor deposition until the predetermined silicon loading is reached. S3. Carbon coating: Carbon source gas is introduced into the fluidized bed reactor to perform carbon coating treatment on the silicon-deposited material to obtain the silicon-carbon composite material.

[0026] The carbon matrix material is one or more of porous carbon, graphite, amorphous carbon, carbon nanotubes, graphene, and carbon fiber, or a mixture thereof.

[0027] The fluidizing agent particles are nanoparticles, coarse particles that are coarser than the carbon matrix, and mixed particles of nanoparticles and coarse particles. The mass ratio of the mixed particles of nanoparticles and coarse particles is not limited.

[0028] The fluidization aid for nanoparticles is one or more of the following: silicon and silicon-containing compounds (such as silicon carbide), high-performance carbon materials (such as graphene, carbon nanotubes, carbon nanofibers), conductive metal powder, metal oxide powder, and modified materials based thereon (such as heteroatom doping modification), pyrolysis reaction catalysts and modified materials based thereon, and the mass mixing ratio of various nanoparticles is not limited.

[0029] The coarse particle fluidization aid is one or more of the following: silicon and silicon-containing compounds (such as silicon carbide), high-performance carbon materials (such as graphene), conductive metal powder, metal oxide powder, and modified materials based thereon (such as heteroatom doping modification), silicon-carbon composite materials and modified materials based thereon, pyrolysis reaction catalysts and modified materials based thereon, and the mass mixing ratio of the various coarse particles is not limited.

[0030] The silicon source gas is one or more of silane, ethylsilane, chlorosilane, and other silicon-containing compounds.

[0031] The carbon source gas is one or more of methane, ethane, ethylene, acetylene, propylene, and other carbon-containing organic compounds.

[0032] In step S2, the chemical vapor deposition process is a continuous reaction, involving multiple deposition-cooling cycles until the predetermined silicon loading is reached.

[0033] The silicon-carbon composite material is used as an active material to prepare the negative electrode sheet for lithium-ion batteries.

[0034] The lithium-ion battery negative electrode sheet can be used as a component of a lithium-ion battery.

[0035] Example 1: Preparation of silicon-carbon composite materials S1. Pretreatment and Mixing: Weigh 100 g of porous carbon (BET specific surface area approximately 2033 m² / g, pore volume 0.92 cm³ / g, micropore ratio 87%, D50 7 μm) and 0.1 g of nano-silicon carbide (SiC, D50 approximately 100 nm) powder. Mix the two thoroughly to ensure that the silicon carbide particles are uniformly loaded on the porous carbon surface.

[0036] S2, Silicon Deposition: The porous carbon material obtained in step (S1) is added to the reactor and heated to 250°C under a nitrogen atmosphere to remove the internal pores of the porous carbon and the air from the reactor. The temperature is then increased to 580°C at a rate of 5°C / min and held for 20 min. Subsequently, the temperature is lowered to 50°C, and step (S2) is repeated to achieve a silicon loading of 50% in the final composite material.

[0037] S3, Carbon Coating: The reactor is heated to 650 ℃ and acetylene gas is introduced and kept at this temperature for 4 h to obtain a silicon-carbon composite anode material with a carbon shell coating on the surface. The thickness of the carbon coating layer is 1-10 nm.

[0038] Example 2: Application of silicon-carbon composite materials in lithium-ion batteries The electrochemical performance of the silicon-based anode materials prepared in the above examples and comparative examples was tested according to the following method: the prepared silicon-carbon composite material, Ketjen black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1 to form a slurry. The slurry was uniformly coated onto a copper foil current collector and dried under vacuum for 12 h to form a working electrode. A lithium sheet was used as the counter electrode, a glass fiber membrane was used as the separator, and 1 mol / L LiPF6 (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) was used as the electrolyte. 1% VC was added to the electrolyte, and the cells were assembled into coin cells in an inert gas glove box under a nitrogen atmosphere.

[0039] It is important to note that the constructions and arrangements of this application shown in several different exemplary embodiments are merely illustrative. Although only a few embodiments are described in detail in this disclosure, those who consult this disclosure will readily understand that many modifications are possible (e.g., changes in the size, dimensions, structure, shape, and proportions of various elements, as well as parameter values ​​(e.g., temperature, pressure, etc.), installation arrangements, use of materials, color, orientation, etc.) without substantially departing from the novel teachings and advantages of the subject matter described in this application. For example, an element shown as integrally formed may be composed of multiple parts or elements, the position of elements may be inverted or otherwise changed, and the nature or number or position of discrete elements may be altered or changed. Therefore, all such modifications are intended to be included within the scope of the invention. The order or sequence of any process or method steps may be changed or rearranged according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure described herein that performs the function, and not only structurally equivalent but also equivalent in structure. Other substitutions, modifications, alterations, and omissions may be made in the design, operation, and arrangement of the exemplary embodiments without departing from the scope of the invention. Therefore, the present invention is not limited to the specific embodiments, but extends to various modifications that still fall within the scope of the appended claims.

[0040] Furthermore, in order to provide a concise description of exemplary embodiments, not all features of actual embodiments (i.e., those features that are not relevant to the best mode of carrying out the invention as currently considered, or those features that are not relevant to implementing the invention) may be omitted.

[0041] It should be understood that numerous specific implementation decisions can be made during the development of any practical implementation, such as in any engineering or design project. Such development efforts may be complex and time-consuming, but for those skilled in the art who benefit from this disclosure, the development effort will be a routine work of design, manufacturing, and production without requiring much experimentation.

[0042] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring, characterized in that, Includes the following steps: S1. Pretreatment and mixing: The carbon matrix material is mixed with fluidizing agent particles accounting for 0.001% to 99% of its mass, so that the fluidizing agent adheres to the surface of the carbon matrix to obtain the modified carbon material. S2, Silicon deposition: The modified carbon material is placed in a fluidized bed reactor without mechanical stirring components, heated to 300-1500°C under an inert atmosphere, and silicon source gas is introduced for chemical vapor deposition until the predetermined silicon loading is reached. S3. Carbon coating: Carbon source gas is introduced into the fluidized bed reactor to perform carbon coating treatment on the silicon-deposited material to obtain the silicon-carbon composite material.

2. The method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to claim 1, characterized in that: The carbon matrix material is one or more of porous carbon, graphite, amorphous carbon, carbon nanotubes, graphene, and carbon fiber, or a mixture thereof.

3. The method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to claim 1, characterized in that: The fluidizing agent particles are nanoparticles, coarse particles (hereinafter referred to as coarse particles) that are larger than the carbon matrix, and mixed particles of nanoparticles and coarse particles. The mass mixing ratio of the mixed particles of nanoparticles and coarse particles is not limited.

4. The method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to claim 3, characterized in that: The nanoparticle fluidization aid is one or more of silicon and silicon-containing compounds, high-performance carbon materials, conductive metal powders, metal oxide powders, and modified materials based thereon, pyrolysis reaction catalysts and modified materials based thereon. The mass mixing ratio of multiple nanoparticles as fluidization aids is not limited.

5. The method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to claim 3, characterized in that: The coarse particle fluidization aid is one or more of silicon and silicon-containing compounds, high-performance carbon materials, conductive metal powders, metal oxide powders, and modified materials based thereon, silicon-carbon composite materials and modified materials based thereon, pyrolysis reaction catalysts and modified materials based thereon, and the mass mixing ratio of multiple coarse particles as fluidization aids is not limited.

6. The method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to claim 1, characterized in that: The silicon source gas is one or more of silane, ethylsilane, chlorosilane, and other silicon-containing compounds.

7. The method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to claim 1, characterized in that: The carbon source gas is one or more of methane, ethane, ethylene, acetylene, propylene, and other carbon-containing organic compounds.

8. The method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to claim 1, characterized in that: In step S2, the chemical vapor deposition process is a continuous operation, and the silicon loading is adjusted through multiple deposition-cooling cycles until a predetermined value is reached.

9. The method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to claim 1, characterized in that: The silicon-carbon composite material is used as the active material to prepare the negative electrode sheet for lithium-ion batteries.

10. The method for preparing silicon-carbon composite materials by fluidized bed CVD without mechanical stirring according to claim 9, characterized in that: The lithium-ion battery negative electrode sheet can be used as a component of a lithium-ion battery.